The Degree of Guilt as the Special Criteria of Individualization of Administrative Responsibility of Legal Entitiesand Individual Entrepreneurs - Aleksandr I. Stakhov (Сибирское юридическое обозрение)
The article reveals the conflicts and uncertainties of the legislative techniques of assessment of guilt and the individualization of administrative responsibility of legal entities and individual entrepreneurs who have made administrative offenses. Proposed system evaluation criteria when making decisions and other decisions of the courts and supervisory bodies of executive power about the choice of alternative administrative penalties, mitigation of the administrative penalty, the exemption from administrative responsibility to determine the degree of guilt of a legal entity and individual entrepreneur, brought to administrative responsibility in the implementation of the state control and supervision.